THE EFFECT OF WORKLOAD AND FINANCIAL COMPENSATION ON WORK MORALE WITH WORK ENGAGEMENT AS A MODERATING VARIABLE - Dahlan, Mardiana; Syahir Natsir; Adfiyani Fadjar (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2024)
This study aims to analyse the effect of workload and financial compensation on work enthusiasm with work engagement as a moderating variable in the expenditure treasurer of the Regional Work Unit (SKPD) of Tojo Una Una Regency. This research is a type of quantitative research, with the census method, namely using forty-one Tojo Una Una Regency SKPD expenditure treasurers as the population. The analytical tool used is SEM-PLS, data collection through google form media. The results of this study indicate that (1) workload has a negative and significant effect on the morale of SKPD expenditure treasurers of Tojo Una Una Regency (2) financial compensation has a positive and significant effect on the morale of SKPD expenditure treasurers of Tojo Una Una Regency (3) work engagement has a negative and significant effect as a moderator of the relationship between workload and morale of SKPD expenditure treasurers of Tojo Una Una Regency (4) work engagement has a positive and significant effect as a moderator of the relationship between financial compensation and morale of SKPD expenditure treasurers of Tojo Una Una Regency (4) work engagement has a positive and significant effect as a moderator of the relationship between financial compensation and morale.